Model Pembelajaran Learning Cycle Kooperatif Tipe STAD untuk Meningkatkan KualitasProses dan Hasil Belajar - Umi Rochayati; Djoko Santoso; Muhammad Munir (Faculty of Engineering, Universitas Negeri Yogyakarta, 2016)
The researcher implemented the Student Centered Learning with the following objectives: (1) to improve the achievementand the quality of the learning process inthe course of Electrical Installation and Machinery through the Cooperative Learning cyclewith Student Teams Achievement Division (STAD); and (2) to describe the response of the students to the implemention. This study was conducted using the classroom action research approach in 2 cycles. Each cycle consisted of planning, action, observation, and reflection. The results showed: (1) the Cooperative Learning cycle with STAD could improve the quality of the learning process, the students were not merely as the object but rather as the subject of the learning. The learning process comprised highly effective learning environment, interactive discussions, opinions sharing activities, motivation, cooperation and communication among the students. The improvement of the achievement was proved by the mean scores in the first and second cycle that were 69.05 and 76.25 respectively; and (2) the students’ feedbacksresulted from the closed questionnaire were 37.5% strongly agree and 62.5% agree to the implementation while from the open questionnaire,the feedbacks were 92.5% positive and 7.5% of the students said it was a waste of time.